Piranea spartii gen.n.sp.n. (Diptera, Cecidomyiidae) in den geschlossenen Blüten von Spartium junceum L. - Franc Janežič (Acta Biologica Slovenica)
The gall midge Piranea spartii gen.n.sp.n. in the closed flowers of Spartium junceum L. is described.